Оптимізація експресії рекомбінантного пластівцевоутворюючого фактора Staphylococcus aureus в клітинах E.coli XLI-blue - Іванова, Вікторія Джанівна; Позур, Володимир Костянтинович (My University, 2002)
За допомогою описаних засобів оптимізовано процес культивування штаму-продуцента рекомбінантного пластівцевоутворюючого фактора S.aureus (E.coli XLI-Blue (pCF41)), внаслідок чого досягнутий високий рівень біосинтезу цього білку (30% всіх клітинних білків) в даній експресійній системі. Experiments for optimization of the clfA gene expression in E.coli XLI-Blue cells were conducted. It has been shown the reducing of the strain efficiency and the elimination of the plasmid during the cultivation of a producer. Several methods for raising the amount of plasmid-containing cells and increasing the yield of recombinant protein were proposed. Bacterial growth medium was selected to make this process more efficient.
Keywords: експресія; пластівцевоутворюючий фактор; золотистий стафілокок; expression; clumping factor; Staphylococcus aureus; кафедра експертизи харчових продуктів